Prevalensi anomali jumlah gigi ditinjau dari radiografi panoramik di RSGM UNHAS Makassar - Barunawaty Yunus; Kahfi Iczanul Iman (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: Abnormalities in the number of teeth is a change of dental structure that arises from abnormalities during tooth formation, can be due to congenital or growth. For anomalies, the number of teeth consists of anadontia and supernumerary teeth. This research is aimed to obtain a general picture of the prevalence of abnormalities in the number of teeth in terms of panoramic radiographs at RSGM UNHAS. Material and Methods: This type of research is observational descriptive and the design of this study is Cross Sectional Study. The research subjects were all panoramic radiographic photo data in the Teaching and Mouth Hospital of Hasanuddin University in the last 1 year. Data is processed in tables and diagrams. Results: The results showed that the majority of anadontia prevalence by sex occurred in women, as a breakdown of hypodontia with a presentation of 68.04%, oligodontia with a presentation of 26.93%, and anadontia with a presentation of 5.21%. The prevalence of anadontia based on the majority age group occurs in the adult age group, as a breakdown of hypodontia with a presentation of 77.73%, oligodontia with a presentation of 21.40%, and anadontia with a presentation of 0.87%. The prevalence of anadontia by month occurred at most in August 2018 with 70 people, while the lowest number was in July 2018 with 1 person. The prevalence of supernumerary teeth based on the majority sex occurs in male patients with a total of 4 people, as detailed mesiodens with 25% presentation, laterodens with 75% presentation, and no distomolar. Conclusion: The prevalence of anomaly deficiency in the number of teeth by sex is most experienced by women, the prevalence of supernumerary teeth is more experienced by men. When viewed from the age group, abnormalities in the number of teeth are most experienced by the adult age group and supernumerary teeth are most experienced by the adolescent age group.